2017
DOI: 10.1038/s41430-017-0048-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conjugated linoleic acid on blood inflammatory markers: a systematic review and meta-analysis on randomized controlled trials

Abstract: This meta-analysis showed that CLA supplementation may increase inflammatory markers (CRP and TNF-α). There are concerns about using CLA supplementation as an anti-obesity agent among the obese population for at least a short duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…While several studies in rodents and cell culture showed CLA is an anti-inflammatory molecule, some authors do not consider that its anti-inflammatory effects have been sufficiently demonstrated in humans [55]. In addition, other studies have clearly marked CLA as a proinflammatory inductor [56,57], indicating that this effect could be greatly heterogeneous depending on physiological conditions, animal species and the dose of CLA. In addition, initial studies in cells showed that CLA, specifically t10,c12, presented ameliorating effects over the production of reactive oxygen species (ROS), correlating to lower gene expression of inflammatory markers [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While several studies in rodents and cell culture showed CLA is an anti-inflammatory molecule, some authors do not consider that its anti-inflammatory effects have been sufficiently demonstrated in humans [55]. In addition, other studies have clearly marked CLA as a proinflammatory inductor [56,57], indicating that this effect could be greatly heterogeneous depending on physiological conditions, animal species and the dose of CLA. In addition, initial studies in cells showed that CLA, specifically t10,c12, presented ameliorating effects over the production of reactive oxygen species (ROS), correlating to lower gene expression of inflammatory markers [58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, initial studies in cells showed that CLA, specifically t10,c12, presented ameliorating effects over the production of reactive oxygen species (ROS), correlating to lower gene expression of inflammatory markers [58]. Some studies in humans revealed consistent improvements in inflammation with a reduction in TNF-α (tumour necrosis factor α) and IL-1β (interleukin 1-β) levels [59], while others found increases in TNF-α values [56]. Thus, although there is no clear consensus of the effect of CLA on inflammation, our results indicated that low doses of CLA have the ability to decrease the gene expression of Ccl2 in the liver as well as the levels of diglycerides, which have been reported as key markers of hepatic inflammation [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…However, no beneficial effects of resveratrol intake on lowering the inflammatory marker C-reactive protein (CRP) were found, neither in a meta-analysis of randomized controlled trial [135] nor in a later accomplished randomized placebo-controlled clinical trial [136]. These data are, however, in contrast with two more recent meta-analyses concluding the CRP-lowering effects of resveratrol use [137,138].…”
Section: Clinical Studies On Resveratrol In the Context Of Cardiovmentioning
confidence: 99%
“…However, the authors observed that participants with lower ω-6 FA intake at baseline seemed to have greater protection, and an increased intake of ω-6 FA may reduce the risk of myocardial infarction (MI) (RR 0.88, 95%CI 0.76 to 1.02). In addition, a meta-analysis (130) of 11 RCTs including 420 subjects showed that conjugated linoleic acid (CLA) supplementation increased blood levels of CRP by 0.89 mg/L (95% CI: 0.11, 1.68; P = 0.025) and TNF-α levels by 0.39 pg/mL (95% CI: 0.23, 0.55; P < 0.0001). Nonetheless, another meta-analysis (131) concluded that CLA supplements had a proinflammatory effect after observing an increase in plasma CRP concentrations and significant reductions in serum adiponectin concentrations independently of the dosage of CLA supplementation (0.63 mg/dL, 95% CI: 0.13, 1.13, heterogeneity P = 0.026; I 2 = 52.3%).…”
Section: Omega-6mentioning
confidence: 99%